Conductive electrospinning dressing with photo-thermal antibacterial function as well as preparation method and application of conductive electrospinning dressing

By doping MXene nanomaterials into the fiber dressings, combined with electrospinning and spraying technology, fiber dressings with photothermal antibacterial and conductive properties were developed, which solved the problems of insufficient antibacterial performance and lack of active regulation of cell behavior in the prior art, and significantly improved the healing efficiency of diabetic wounds.

CN119838042APending Publication Date: 2025-04-18THE SECOND AFFILIATED HOSPITAL TO NANCHANG UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510324595.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has insufficient antibacterial properties when treating diabetic wounds, making it difficult to effectively deal with drug-resistant bacteria infections, and lacks the ability to actively regulate cellular behavior, making it difficult to meet the complex needs of diabetic wound healing.

Method used

Using fiber dressings based on silk fibroin, polylactic acid and MXene-Ti3C2Tx, MXene nanomaterials are doped in the fiber membrane through electrospinning and electrostatic spraying technology to form wound dressings with photothermal antibacterial properties and conductive properties.

Benefits of technology

This dressing not only has a significant antibacterial effect under the action of photothermal, but also can promote the proliferation and migration of skin cells through conductivity, significantly improving the healing efficiency of diabetic wounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838042A_ABST
    Figure CN119838042A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibacterial materials, and particularly relates to a conductive electrospinning dressing with a photo-thermal antibacterial function and a preparation method and application of the conductive electrospinning dressing. The method comprises the following steps: dispersing Ti < 3 > C < 2 > T < x >-Mxene into hexafluoroisopropanol to obtain an MXene-HFIP solution; then adding and mixing with silk fibroin and poly (L-lactide), and stirring to obtain a spinning solution; placing the spinning solution in an electrostatic spinning device for electrostatic spinning to obtain silk fibers; then putting into a methanol solution to induce conformation transformation, and washing to obtain a nanofiber membrane; the preparation method comprises the following steps: dispersing Ti < 3 > C < 2 > T < x >-Mxene into an ethanol solution to obtain a spraying solution; the spraying liquid is placed in an injector and then sprayed to any surface of the nanofiber membrane through electrostatic spraying, and the conductive electrospinning dressing is obtained. The nanofiber achieves the effects of resisting bacteria and promoting healing of diabetic wounds, and the nanofiber is good in biocompatibility, high in biological safety and very suitable for resisting bacteria and promoting healing of the wounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of antibacterial materials, and specifically relates to a conductive electrospun dressing with photothermal antibacterial properties, and a preparation method and application thereof. Background Art

[0002] Diabetic wounds pose a serious challenge to healing due to increased bacterial susceptibility and suppressed cell proliferation. Effective healing requires both the elimination of bacteria and the stimulation of fibroblast proliferation and migration. However, existing technologies still have many limitations: for example, traditional dressings have insufficient antibacterial properties and are prone to infection, especially infection by drug-resistant bacteria; in addition, traditional dressings mainly participate in the passive healing process and lack the ability to actively regulate cell behavior, making it difficult to meet the complex needs of diabetic wound healing.

[0003] Photothermal antimicrobial therapy (PTT) uses light energy to convert into local heat energy to promote the decomposition of bacterial structures, thereby achieving antibacterial properties. However, when photothermal materials are used alone, they are prone to aggregation, which affects the efficiency of photothermal conversion. Electrical stimulation (ES) can regulate skin cell behavior and improve cell proliferation and migration capabilities, but it lacks active antibacterial capabilities and is difficult to effectively deal with wound infection problems. Therefore, it is of great clinical significance to develop a new wound dressing that can simultaneously have the functions of highly efficient antibacterial and promoting cell proliferation and migration. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a conductive electrospun dressing with photothermal antibacterial properties and a preparation method and application thereof, specifically adopting the following technical solutions: In a first aspect, the present invention provides a method for preparing a conductive electrospun dressing having photothermal antibacterial properties, comprising the following steps: Dispersing Ti3C2Tx-Mxene in hexafluoroisopropanol to obtain MXene-HFIP solution; Adding silk fibroin and poly-L-lactide to the MXene-HFIP solution and stirring to obtain a spinning solution; placing the spinning solution in an electrospinning device for electrospinning to obtain silk fibers; placing the silk fiber in a methanol solution to induce conformational change, and washing to obtain a nanofiber membrane; Dispersing Ti3C2Tx-Mxene in an ethanol solution to obtain a spraying solution; The spraying liquid is placed in a syringe and then sprayed onto any surface of the nanofiber membrane by electrostatic spraying to obtain the conductive electrospun dressing with photothermal antibacterial properties.

[0005] The present invention provides a fiber dressing based on silk fibroin, polylactic acid and MXene-Ti3C2Tx. The high conductivity and photothermal properties of MXene-Ti3C2Tx are used to prepare a wound dressing with both photothermal antibacterial properties and electrical conductivity, and two active regulation methods are used for synergistic treatment. The dressing can electrically regulate cell behavior, has electrical conductivity, can promote active healing of skin wounds under external electrical stimulation, and can efficiently kill local pathogens through photothermal effect, promoting the healing of infectious diabetic wounds.

[0006] As a further preferred embodiment, the added amounts of the Ti3C2Tx-Mxene, the silk fibroin and the poly-L-lactide are 1 wt.%, 5 wt.% and 5 wt.% of the spinning solution, respectively.

[0007] As a further preferred embodiment, the silk fibroin is obtained by the following steps: The silk cocoons are placed in a Na2CO3 aqueous solution and boiled, washed, dried, dissolved in a LiBr aqueous solution, dialyzed using a semipermeable membrane at room temperature for 72 hours, and freeze-dried to obtain the silk fibroin solid.

[0008] As a further preferred embodiment, the concentration of the LiBr aqueous solution is 9.3 M.

[0009] As a further preferred embodiment, the drying is performed in an oven, and the drying temperature is 55°C-70°C.

[0010] As a further preferred embodiment, the specific conditions for electrospinning by placing the spinning solution in an electrospinning device are: The injection rate of the spinning solution is 1 mL / h, the needle voltage is 14 kV, the distance between the needle tip and the receiver is 15 cm, and the spinning time is 2 hours. In the above preparation process, the change of these parameters will affect the stability of the Taylor cone during the spinning process, resulting in poor fiber membrane structure.

[0011] As a further preferred embodiment, the specific parameter conditions of the electrostatic spraying are: The needle voltage of the syringe is 10 kV; the injection rate of the syringe is 1 mL / h.

[0012] In a second aspect, the present invention provides a conductive electrospun dressing with photothermal antibacterial properties, and the conductive electrospun dressing with photothermal antibacterial properties is prepared by the above method.

[0013] In a third aspect, the present invention provides the use of the above-mentioned conductive electrospun dressing with photothermal antibacterial properties in the preparation of products for treating diabetic wounds.

[0014] In a fourth aspect, the present invention provides a product for treating diabetic wounds, the product comprising the above-mentioned conductive electrospun dressing with photothermal antibacterial properties.

[0015] The beneficial effects of the present invention are: The present invention uses silk protein and poly-L-lactide as the main materials of the nanofiber membrane, which has excellent mechanical strength, hydrophilicity, biocompatibility and no toxic side effects. MXene nanomaterials are doped into the nanofiber membrane by electrostatic spinning technology, while further enhancing the above characteristics, a microenvironment more suitable for fibroblast adhesion and proliferation is provided in the microstructure. Further, the MXene nanomaterial is uniformly attached to the surface of the nanofiber structure by electrostatic spraying technology, giving the material excellent photothermal and electrical conductivity. The various components of the nanofiber provided by the present invention act synergistically, wherein poly-L-lactide provides excellent mechanical strength, and the addition of silk protein gives the fiber membrane better biocompatibility and hydrophilicity. According to the experimental results of the present invention, the fiber dressing prepared by the present invention can convert light energy into heat energy for photothermal therapy under the irradiation of near-infrared light, and has a good antibacterial effect. The fiber dressing has excellent electrical conductivity and has the ability to transmit in vitro electrical stimulation to the inside of damaged tissue. The invention achieves the effects of antibacterial and promoting diabetic wound healing, and the nanofiber has good biocompatibility and high biosafety, and is very suitable for antibacterial and promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 This is a scanning electron microscope image (SEM) of the conductive electrospun dressing with photothermal antibacterial properties provided in Example 1 of the present application; Figure 2 The water contact angle and conductivity measurement results of the fiber dressing provided in Example 2 of the present application; Figure 3 is the photothermal performance measurement result of the fiber dressing provided in Example 3 of the present application; Figure 4 The effect of the photothermal properties of different fiber membrane materials on the antibacterial effect provided in Example 4 of the present application; Figure 5 The results of biocompatibility tests using L929 cells on different fiber membrane materials provided in Example 5 of the present application; Figure 6These are wound photos of the treatment process of the diabetic wound infection model using different nanofibers provided in Example 6 of the present application. DETAILED DESCRIPTION

[0018] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] Example 1 A method for preparing a conductive electrospun dressing with photothermal antibacterial properties, comprising the following steps: Step 1: Cut the silk cocoons into small pieces and immerse them in a Na2CO3 aqueous solution for boiling. Then wash them with deionized water, dry them in a 60°C oven, and dissolve them in a 9.3 M LiBr aqueous solution. Use a semipermeable membrane (12 kDa MWCO) to dialyze them against deionized water at room temperature for 72 hours, and finally freeze-dry them to obtain white silk fibroin solid (SF). Step 2: Ti3C2Tx-Mxene (added in an amount of 1 wt.% of the spinning solution) was well dispersed in hexafluoroisopropanol (HFIP) by a magnetic stirrer to obtain a MXene-HFIP solution; Step 3: Add silk fibroin (SF, added in an amount of 5 wt.% of the spinning solution) and poly-L-lactide (PLLA, added in an amount of 5 wt.% of the spinning solution) to the prepared MXene-HFIP solution and slowly stir to obtain a spinning solution (denoted as SPM); Step 4: The prepared spinning solution (SPM) was sucked into a 5 mL plastic syringe with a metal needle (diameter = 0.51 mm), placed in an electrospinning device, and the fiber was electrospun at a voltage of 14 kV using a digital syringe pump (New Era Pump System, Inc; USA). The injection rate of the spinning solution was 1 mL / h, and the silk fiber was collected using a drum collector (1500 r / min), with the needle tip at a distance of 15 cm from the receiver; Step 5: The silk fibers collected by electrospinning were placed in anhydrous methanol for 10 min to induce conformational transition, and then washed with distilled water at 37 °C to obtain nanofibrous membranes (SPM); Step 6: Disperse Ti3C2Tx-Mxene (1 wt.%) in a water-ethanol (1:1) mixed solution and use a 5 mL plastic syringe with a metal needle at 10 kV, 1 mL / min. −1The parameters were electrostatically sprayed on a certain surface of SPM, and the nanofiber membrane obtained after electrostatic spraying obtained a conductive electrospun dressing (SPM-M) with photothermal antibacterial properties.

[0020] The surface morphology of the conductive electrospun dressing (SPM-M) with photothermal antibacterial properties prepared by the present invention is investigated, specifically including the following: The surface morphology of the electrospun fibers was observed by field emission scanning electron microscopy (FESEM, Hitachi SU8100, Japan). The fiber diameter was measured using Image J software (NIH, USA). Figure 1 As shown in the figure, it can be seen that the silk fibroin / polylactic acid composite fiber presents a nanofiber structure with a diameter of about 800nm. The ultra-thin single-layer sheet structure of MXene is well loaded on the surface of each fiber through electrostatic spraying, indicating the successful synthesis of the material.

[0021] Comparative Example 1 A method for preparing a conductive electrospun dressing with photothermal antibacterial properties, comprising the following steps: Step 1: Cut the silk cocoons into small pieces and immerse them in a Na2CO3 aqueous solution for boiling. Then wash them with deionized water, dry them in a 60°C oven, and dissolve them in a 9.3 M LiBr aqueous solution. Use a semipermeable membrane (12 kDa MWCO) to dialyze them against deionized water at room temperature for 72 hours, and finally freeze-dry them to obtain white silk fibroin solid (SF). Step 2: Dissolve the prepared silk fibroin (SF, 5 wt.%) in hexafluoroisopropanol (HFIP) and stir slowly for 12 h to obtain SF-HFIP solution; Step 3: dissolving poly (L-lactide) (PLLA, 5 wt.%) in the prepared SF-HFIP solution to prepare a mixed solution and slowly stirring for 12 h to obtain a mixed solution of silk fibroin and poly (L-lactide) (SP solution); Step 4: The prepared mixed solution of silk fibroin and poly-L-lactide (SP) was sucked into a 5 mL plastic syringe with a metal needle (diameter = 0.51 mm), placed in an electrospinning device, and the fiber was electrospun at a voltage of 14 kV using a digital syringe pump (New EraPump System, Inc; USA). The injection rate of the spinning solution was 1 mL / h, and the silk fibers were collected using a drum collector (1500 r / min), with the needle tip at a distance of 15 cm from the receiver; Step 5: The silk fibers collected by electrospinning were placed in anhydrous methanol for 10 min to induce conformational transition, and then washed with distilled water at 37 °C to obtain nanofiber membrane (SP); Step 6: Disperse Ti3C2Tx-Mxene (1 wt.%) in a water-ethanol (1:1) mixed solution and use a 5 mL plastic syringe with a metal needle at 10 kV, 1 mL / min. -1 The parameters were electrostatically sprayed on a certain surface of SP, and the nanofiber membrane obtained after electrostatic spraying obtained a conductive electrospun dressing (SP-M).

[0022] Comparative Example 2 A method for preparing a conductive electrospun dressing with photothermal antibacterial properties, comprising the following steps: Step 1: Cut the silk cocoons into small pieces and immerse them in a Na2CO3 aqueous solution for boiling. Then wash them with deionized water, dry them in a 60°C oven, and dissolve them in a 9.3 M LiBr aqueous solution. Use a semipermeable membrane (12 kDa MWCO) to dialyze them against deionized water at room temperature for 72 hours, and finally freeze-dry them to obtain white silk fibroin solid (SF). Step 2: Dissolve the prepared silk fibroin (SF, 5 wt.%) in hexafluoroisopropanol (HFIP) and stir slowly for 12 h to obtain SF-HFIP solution; Step 3: dissolving poly (L-lactide) (PLLA, 5 wt.%) in the prepared SF-HFIP solution to prepare a mixed solution and slowly stirring for 12 h to obtain a mixed solution of silk fibroin and poly (L-lactide) (SP solution); Step 4: The prepared mixed solution of silk fibroin and poly-L-lactide (SP) was sucked into a 5 mL plastic syringe with a metal needle (diameter = 0.51 mm), placed in an electrospinning device, and the fiber was electrospun at a voltage of 14 kV using a digital syringe pump (New EraPump System, Inc; USA). The injection rate of the spinning solution was 1 mL / h, and the silk fibers were collected using a drum collector (1500 r / min), with the needle tip at a distance of 15 cm from the receiver; Step 5: The silk fibers collected by electrospinning were placed in anhydrous methanol for 10 min to induce conformational transition, and then washed with distilled water at 37 °C to obtain a conductive electrospun dressing (SP); Comparative Example 3 A method for preparing a conductive electrospun dressing with photothermal antibacterial properties, comprising the following steps: Step 1: Cut the silk cocoons into small pieces and immerse them in a Na2CO3 aqueous solution for boiling. Then wash them with deionized water, dry them in a 60°C oven, and dissolve them in a 9.3 M LiBr aqueous solution. Use a semipermeable membrane (12 kDa MWCO) to dialyze them against deionized water at room temperature for 72 hours, and finally freeze-dry them to obtain white silk fibroin solid (SF). Step 2: Ti3C2Tx-Mxene (1 wt.%) was well dispersed in hexafluoroisopropanol (HFIP) by a magnetic stirrer to obtain MXene-HFIP solution; Step 3: Add silk fibroin (SF, 5 wt.%) and poly-L-lactide (PLLA, 5 wt.%) to the prepared MXene-HFIP solution and stir slowly to obtain a spinning solution (denoted as SPM); Step 4: The prepared spinning solution (SPM) was sucked into a 5 mL plastic syringe with a metal needle (diameter = 0.51 mm), placed in an electrospinning device, and the fiber was electrospun at a voltage of 14 kV using a digital syringe pump (New Era Pump System, Inc; USA). The injection rate of the spinning solution was 1 mL / h, and the silk fiber was collected using a drum collector (1500 r / min), with the needle tip at a distance of 15 cm from the receiver; Step 5: The silk fibers collected by electrospinning were placed in anhydrous methanol for 10 min to induce conformational transition, and then washed with distilled water at 37 °C to obtain nanofibrous membranes (SPM); Example 2 The relevant properties of the SP, SPM, SP-M, and SPM-M samples prepared in the above Example 1 and the comparative example are explored, and the specific properties are as follows: (1) The hydrophobicity of electrospun fibers was measured using a contact angle analyzer (JY-82C). Figure 2 Figure a shows that the SP contact angle is 112.41°, and the contact angle of the SPM fiber membrane after adding Ti3C2Tx-Mxene drops to 52.52°. After spraying Ti3C2Tx-Mxene on the surface of the SP fiber membrane, the contact angle continues to drop to 33.64°. The SPM-M group fiber membrane exhibits the smallest contact angle of 27.53°, which indicates that the hydrophilicity of the fiber dressing increases with the addition of MXene.

[0023] (2) The conductivity of different nanofilms was measured by a dual-probe benchtop digital multimeter (34450A, Keysight Technologies, USA). The results are shown in Figure 2 As shown in b, it can be seen from the figure that SP does not have conductive ability. With the addition of MXene, the conductivity of the fiber dressing increases. After MXene is attached to the fiber surface by electrostatic spraying, the conductivity of the fiber dressing increases significantly, showing the excellent conductivity of the material.

[0024] Example 3 In order to evaluate the photothermal performance of each group of nanofiber membranes, the SP, SPM, SP-M, and SPM-M samples prepared in Example 1 and the comparative example were heated at 0.5 W / cm 2 The power density of the laser was irradiated with an 808 nm laser (LOS-BLD-808-15W-C / P, Hitech Optoelectronics) for 90 s. To determine the NIR laser power density on the nanofiber membrane, the laser output power was set to 0.5 W, and the fiber collimator of the 808 nm laser (LOS-BLD-808-15W-C / P, Hitech Optoelectronics) was adjusted to produce a spot diameter of 1.13 cm, corresponding to 1 cm 2 Therefore, the power density is kept at the specified 0.5 W / cm 2 The maximum temperature of the sample within 90 seconds was recorded using an infrared thermal imager (DT980, CEM).

[0025] The results are as follows Figure 3 As shown in the figure, it can be seen that at 0.5W / cm 2 The results showed that after 90 seconds of laser irradiation, the temperature of the fiber membranes in the SPM, SP-M, and SPM-M groups increased to varying degrees, with the SPM-M group increasing most significantly, reaching 58.7±0.26°C, the SP-M group reaching 55.4±0.55°C, and the SPM group reaching 52.5±0.2°C, indicating that the fiber membranes prepared by the present invention have good photothermal properties.

[0026] Example 4 Antibacterial test In this example, Staphylococcus aureus (MSSA, ATCC 25923), methicillin-resistant Staphylococcus aureus (MRSA, ATCC 43300) and Escherichia coli (EC, ATCC 25922) were used to explore the effect of photothermal time on the antibacterial effect of electrospun fiber membranes, and SP, SPM, SP-M and SPM-M were selected as samples. Each group of sample films was prepared into a disc with a diameter of 10 mm, and then washed with phosphate buffered saline (PBS) after ethanol soaking to remove residual ethanol, and then placed in a vertical flow clean bench for ultraviolet (UV) irradiation. The bacteria were cultured in (Luria-Bertani) broth for 24 hours (1×10 -7 cfu / mL). Subsequently, 100 μL of bacterial solution was added to the surface of the two groups of samples. Then, an 808 nm NIR laser (power density of 0.5 W / cm 2) The infiltrated electrospun fiber membranes of each group were irradiated for 5 min. After irradiation, the fiber membranes were placed in 1 mL PBS (pH = 7.4) and shaken to obtain a bacterial suspension. The obtained bacterial suspension was diluted 100 times and 50 μL of the bacterial suspension was evenly spread on a fresh LB agar plate, repeated three times, and cultured at 37 ° C for 16 hours. ImageJ software (v1.53) was used to record and measure the number of colonies. The bacterial survival rate was calculated according to the following formula: Bacterial survival rate (%) = (number of colonies in the experimental group / number of colonies in the control group) × 100% The results are as follows Figure 4 a and Figure 4 As shown in b, there is no statistical difference in bacterial survival rate between the SP group and the SP-M group, indicating that SP-M has no bactericidal effect under 808nm laser irradiation. The bacterial survival rate of the SPM group is 25%, indicating that blending MXene in SP significantly improves the bactericidal effect of the composite fiber membrane. The SPM-M group showed the strongest bactericidal effect, as shown in Figure 4 The number of colonies on the LB plate shown in a is the least, and the bacterial survival rate of each group is below 1%, indicating that the most significant antibacterial effect is achieved after blending and spraying MXene.

[0027] Example 5 Biocompatibility assay L929 cells were inoculated on different electrospun films (SP, SPM, SP-M, and SPM-M were samples), and the culture environment was 37°C and 5% CO2. The culture medium was replaced every 2-3 days. The SP, SPM, SP-M, and SPM-M sample films were prepared into discs with a diameter of 10 mm. The sample membranes were soaked in ethanol and then washed with phosphate buffered saline (PBS) to remove the residual ethanol. Then, they were placed in a vertical flow clean bench for ultraviolet (UV) irradiation. After disinfection, the discs were placed in a 24-well cell culture plate equipped with a slide, and L929 cells were cultured at a rate of 2×10 4 The density of cells / well was inoculated on different sample membranes, and DMEM culture medium containing 10% fetal bovine serum was added. On the 1st and 5th days of culture on each group of samples, the cell viability was detected using the CCK-8 kit, and 100 μl of CCK-8 solution and 900 μl of DMEM culture medium were added to each well and incubated at 37°C in the dark for 1 hour. Subsequently, the absorbance was detected at 450 nm using a microplate reader.

[0028] Cell viability (%) = absorbance value of experimental group / absorbance value of control group × 100% The results are as follows Figure 5As shown, the cell viability of the SP, SPM, SP-M and SPM-M samples was greater than 80%, indicating that each group of materials had no toxic side effects on cells and had good biocompatibility.

[0029] Example 6 To investigate the therapeutic effects of different nanofibers (SP, SPM, SP-M, SPM-M) on the diabetic wound infection model A total of 24 Sprague-Dawley male rats (average body weight, 250 g) were used as experimental animals and assigned to five experimental groups: Tegaderm film (as a control, 3M, USA), SPM-M, SPM-M + NIR (combined with 808 nm NIR irradiation), SPM-M + ES (combined with exogenous electrical stimulation), and SPM-M + NIR + ES (combined with 808 nm NIR irradiation and exogenous electrical stimulation). The rats were anesthetized by intraperitoneal injection of 3% pentobarbital (100 μL / 100 g body weight). After shaving and disinfection, a full-thickness circular skin defect with a diameter of 10 mm was made on the back of the rats. Then, 20.0 μL of Staphylococcus aureus suspension (1×10 8 CFU / mL) was added to the back of each skin-defective mouse. The wound was covered with gauze for 6-8 hours to ensure wound infection. The control group used commercially available Tegaderm film to cover the wound, the experimental group used sterilized SPM-M samples to cover the wound, and the combined NIR group used 808 nm NIR light (0.5 W / cm 2 The wound site was irradiated with a pulsed electrical signal (25 Hz, 50% duty cycle, 20 min) in the combined ES group. The wounds of the mice were recorded regularly, and the wound areas on different days were calibrated using ImageJ software (v1.53) (the wounds of the mice were recorded regularly on the 1st, 4th, 7th, 11th and 14th days of the experiment). The wound healing efficiency uses the relative wound area, and the formula is: Relative wound area (%) = (wound area on day t / wound area on day 0) × 100% (t = 1, 4, 7, 11, 14).

[0030] The results are as follows Figure 6 As shown (where Figure 6 a in Figure 6 b in Figure 6 c in Figure 6 In d, Figure 6e in the figure represent the control group, SPM-M group, SPM-M + NIR group, SPM-M + ES group and SPM-M + NIR + ES group, respectively). On the 14th day of treatment, the healing rates of the control group and the SPM-M group were 71.4% and 76.8%, respectively, with no statistical difference between the two groups, indicating that the prepared dressing had equivalent performance to the control group film. The healing rates of the SPM-M + NIR and SPM-M + ES groups were 79.5% and 82.8%, respectively, which were significantly improved compared with the control group and the SPM-M group, indicating that the SPM-M dressing combined with NIR or ES treatment has a significant promoting effect on diabetic wound healing, while there is no significant difference between the two. The wound healing rate of the SPM-M + NIR + ES group reached 98.7%, the highest among all treatment groups, and was statistically different from the control, SPM-M, SPM-M + NIR, and SPM-M + ES. This indicates that SPM-M combined with NIR and ES treatment significantly improved the wound healing rate, and the prepared nanofiber dressing has an excellent wound healing effect.

[0031] The embodiments of the present application are described above in conjunction with the accompanying drawings. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the core idea of ​​the present application, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the inspiration of the present application, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present application and the claims, all of which are within the protection of the present application.

Claims

1. A method for preparing a conductive electrospun dressing with photothermal antibacterial properties, characterized in that: The following steps are involved: Dispersing Ti3C2Tx-Mxene in hexafluoroisopropanol to obtain MXene-HFIP solution; Adding silk fibroin and poly-L-lactide to the MXene-HFIP solution and stirring to obtain a spinning solution; placing the spinning solution in an electrospinning device for electrospinning to obtain silk fibers; placing the silk fiber in a methanol solution to induce conformational change, and washing to obtain a nanofiber membrane; Dispersing Ti3C2Tx-Mxene in an ethanol solution to obtain a spraying solution; The spraying liquid is placed in a syringe and then sprayed onto any surface of the nanofiber membrane by electrostatic spraying to obtain the conductive electrospun dressing with photothermal antibacterial properties.

2. The preparation method according to claim 1, characterized in that The added amounts of the Ti3C2Tx-Mxene, the silk fibroin and the poly-L-lactide are 1 wt.%, 5 wt.% and 5 wt.% of the spinning solution, respectively.

3. The preparation method according to claim 2, characterized in that: The silk fibroin is obtained by the following steps: The silk cocoons are placed in a Na2CO3 aqueous solution and boiled, washed, dried, dissolved in a LiBr aqueous solution, dialyzed at room temperature for 72 hours using a semipermeable membrane, and freeze-dried to obtain the silk fibroin solid.

4. The preparation method according to claim 3, characterized in that: The concentration of the LiBr aqueous solution is 9.3M.

5. The preparation method according to claim 3, characterized in that: The drying is performed in an oven at a temperature of 55°C-70°C.

6. The preparation method according to claim 1, characterized in that: The specific conditions for electrospinning by placing the spinning solution in an electrospinning device are as follows: The injection rate of the spinning solution is 1 mL / h, the needle voltage is 14 kV, the distance between the needle tip and the receiver is 15 cm, and the spinning time is 2 h.

7. The preparation method according to claim 1, characterized in that: The specific parameter conditions of the electrostatic spraying are: The needle voltage of the syringe is 10 kV; the injection rate of the syringe is 1 mL / h.

8. A conductive electrospun dressing with photothermal antibacterial properties, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the conductive electrospun dressing with photothermal antibacterial properties as claimed in claim 8 in the preparation of products for treating diabetic wounds.

10. A product for treating diabetic wounds, characterized in that: It includes the conductive electrospun dressing with photothermal antibacterial properties as described in claim 8.

Citation Information

Patent Citations

  • Preparation method of silk fibroin wound dressing based on MXene enhancement

    CN111925557A

  • MXene hybrid nanofiber as well as preparation method and application thereof

    CN118390184A

  • Preparation and application of Ti3C2Tx MXene-based conductive antibacterial hydrogel dressing

    CN118718080A

  • Multifunctional hydrogel for promoting healing of diabetic wound and preparation method thereof

    CN119280399A

  • Conductive Hydrogel-Based Wearable Health Monitors

    US20230397870A1